REVIEW OF THE STATE OF DESCENT SYSTEM IN CONTEMPORARY EDDA, EBONYI STATE, NIGERIA - Onwuka, Julius Okechukwu; Uduka, Uchenna Kalu; Ikonne, Ogadinma; Duru, Fidelia Amara; Nwaugo, Valentine (African Journal of Social and Behavioural Sciences, 2024)
Descent is a recognized link between a person and his/her ancestors. It is the system by which members of a society trace kinship over generations. Many societies of Africa especially within the southeastern region of Nigeria are predominantly described as patrilineal, however, few of such societies especially in Abia and Ebonyi States have been identified to have traces of matrilineal and patrilineal characteristics according to Anthropologists. However, many old literatures erroneously described these few societies as matrilineal which have affected the perception of these societies as abnormal by the predominant patrilineal societies. This study was aimed at identifying in a survey the current state of descent of these societies using the indicators of descent like community membership, inheritance, residence, succession and authority in Edda community in present-day Ebonyi State. The study purposely sampled 130 respondents made up of titled men and women, opinion moulders male and female and youth groups male and female who formed focus group discussants and interviewees from four randomly selected villages (Amangwu, Osisioma, Nguzu and Ekoli) of the eleven Edda villages that has a population of about 4,350,000 projected from the 2006 population census. It found that Edda is 80% patriliny and 20% matriliny with a future descent towards fully patrilineal and therefore moves away from the findings of Otternberg (1968) who described the society as matrilineal.